Glucose Variability: Where It Is Important and How to Measure It - DeVries, J. Hans (American Diabetes Association, 2013)
Glucose variability predicts hypoglycemia in both type 1 and type 2 diabetes and has consistently been related to mortality in nondiabetic patients in the intensive care unit. SD and mean amplitude of glycemic excursions have historically been very popular measures of glucose variability. For reasons outlined in this counterpoint, I propose to use coefficient of variation and the mean absolute glucose change as preferred measures of glucose variability.